From Long‐ to Short‐Term Inter‐Plate Coupling at the Subducted Carnegie Ridge Crest, Offshore Central Ecuador. Issue 8 (19th August 2022) - Collot, J.‐Y.; Proust, J.‐N.; Nocquet, J.‐M.; Martillo, C.; Michaud, F.; Lebrun, J.‐F.; Schenini, L.; Popescu, S.; Hernandez, M.‐J.; Ratzov, G.
Abstract: We investigate the relationship between the long‐term (Quaternary) interplate coupling and the short‐term geodetically derived interseismic coupling at the Central Ecuador subduction zone. At this nonaccretionary margin, the Cabo Pasado shelf promontory and coastal area are associated with two inter‐plate geodetically locked patches. The deepest patch ruptured co‐seismically during the Mw7.8‐2016 Pedernales earthquake, while the shallowest underwent dominantly after‐slip. Marine geophysical and chronostratigraphic data allow reconstructing the Quaternary tectonic evolution of the shelf promontory and substantiating variation of the long‐term inter‐plate coupling that led to the geodetically locked patches. Prior to ∼1.8 Ma, the outer‐wedge inter‐plate coupling was strong enough to activate trench‐subparallel strike‐slip faults. Then, between ∼1.8 and 0.79 Ma, shortening and uplift affected the shelf promontory, implying a locally increased inter‐plate coupling. After a short, post‐0.79 Ma period of subsidence, shortening and uplift resumed denoting a high inter‐plate coupling that endured up to the present. The synchronicity of the structural evolution of the shelf promontory with the subduction chronology of two reliefs of the Carnegie Ridge crest suggests that the locked patches are caused by a geometrical resistance to subduction that propagates landward causing permanent deformation. In 2016, the deepest subducted relief localized stress accumulation and high seismic slip, while the shallowest relief, which is associated with a weakened outer‐wedge, prevented updip rupture propagation. Thus, at nonaccretionary margins, active outer‐wedge strike‐slip faults might be considered a proxy of near‐trench coupling, and subducted relief a cause of plate coupling but an obstacle to the tsunami genesis when the relief is shallow. Plain Language Summary: The 2016‐Ecuador earthquake ruptured a subduction fault segment previously locked for decades beneath the coastline. The rupture was arrested updip by another locked fault segment called locked patch, which instead slipped slowly. To understand the cause of the locked patches, their rupture behaviors, and whether the decadal fault locking and long‐term subduction processes are related, we reconstructed the Quaternary tectonic evolution of the margin offshore Central Ecuador using geophysical data. We consider that tectonic deformation reflects the long‐term inter‐plate coupling, which is the ability of the fault to transfer long‐term stress and strain to the margin. Prior to ∼1.8 Ma, a trench‐subparallel fault accommodating lateral displacement indicates a shallow plate coupling, which increased locally between ∼1.8 and 0.79 Ma as shown by margin shortening. After a brief subsidence, shortening resumed, denoting a strong coupling that persisted until today in the form of the locked patches. Although many physical factors have been proposed to control plate coupling, here we find that the locked patches are caused by the subduction of two reliefs of a submarine ridge. Remarkably, in 2016, the deepest relief released high elastic strain, while the shallower relief, thrust under a weakened outer‐margin, damped updip rupture propagation, impeding a significant tsunami. Key Points: A trench‐parallel strike‐slip fault and its earthquake‐controlled fault scarps substantiate a pre‐1.8 Ma, outer‐wedge inter‐plate coupling From 1.8 Ma, a robust shelf uplift caused by subducted reliefs highlights a long‐term coupling that led to geodetically locked patches The shallowest subducted relief likely impeded the generation of a major tsunami during the Mw 7.8, 2016 event